Advances in nanocarriers to improve the stability of dsRNA in the environment - Yang, Wenling; Wang, Baitao; Lei, Gao; Chen, Guocan; Liu, Dehai (Frontiers in Bioengineering and Biotechnology, 2022)
RNAi technology, known as a revolutionary technology in the history of pesticides, has been identified as a very promising novel approach for crop protection, which is of great significance for achieving the sustainable agricultural development of the United Nations Food and Agriculture Organization. Although many studies have shown that RNA biopesticides have strong application prospects, its stability seriously restricts the commercial use. As the core component of RNAi, double-stranded RNA (dsRNA) is unstable in its natural form. Therefore, how to ensure the stability of dsRNA is one of the most significant challenges in realizing the commercial use of RNA biopesticides. Nanomaterials such as cationic polymers and lipofectamine can improve the stability of dsRNA in the environment, which has been proved. This paper reviews the recent research progress of nanomaterials that can be used to improve the environmental stability of dsRNA, and discusses the advantages and limitations of different nanomaterials combined with dsRNA, which provides reference for the selection of dsRNA nanoformulations.